Covid-19 Vaccines in Iraq (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
The emergence of the new corona virus ("SARS-CoV-2") in the late 2019 threatened the whole world and scientists throughout the word began searching for biological activities of the virus , During an unprecedented record period that did not exceed one year,  scientists were able to develop a number of safe and effective vaccines  , which have been tested on tens of thousands of volunteers around the world.  Different companies prepared many vaccines and few of them get emergency approval by Food and Drug Administration (FDA) and used in different countries. The aim of the current study is to describe COVID 19 vaccines, structures, efficacy and safety  used in Iraq. Three vaccines (Pfizer,Biontech vaccine, AstraZenica,Oxford vaccine and Sinopharm,vaccine) are used to vaccinate people. All used vaccines showed variable effectiveness with different antibody titers. The ideal vaccine should be cheap, prophylactic, prevent congenital abnormalities, control the disease and eradicate it and be effective at all ages, at different health conditions and its effect is its effect lasts for a long time.